1978
DOI: 10.3758/bf03199539
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary automatic processing in color-naming tasks

Abstract: The automatic processing hypothesis holds that very familiar items are processed involuntarily, and two color-naming experiments were designed to test this further. Experiment 1 employed words as written stimuli and focal and nonfocal colors as inks. Supporting the automatic processing hypothesis, neutral words delayed color naming, indicating that their representations were activated involuntarily. There was no interaction of ink type and written item conditions. Experiment 2 employed single letters as writte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
1
3

Year Published

1982
1982
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 14 publications
6
67
1
3
Order By: Relevance
“…Adding unrelated letters to the first letters did not alter interference, leading Singer et al to speculate that the interference stemmed from activation of a motor program to articulate the beginning of a word. Regan (1978) confirmed this initial-letter effect, also showing that the first letter could produce facilitation in the congruent case. She took this as evidence for automatic processing of letters and words.…”
Section: Acoustic Variationsupporting
confidence: 71%
See 2 more Smart Citations
“…Adding unrelated letters to the first letters did not alter interference, leading Singer et al to speculate that the interference stemmed from activation of a motor program to articulate the beginning of a word. Regan (1978) confirmed this initial-letter effect, also showing that the first letter could produce facilitation in the congruent case. She took this as evidence for automatic processing of letters and words.…”
Section: Acoustic Variationsupporting
confidence: 71%
“…McCown and Arnoult (1981) printed the stimuli vertically versus horizontally using either the entire color word or just its first three letters, and reported equivalent interference in all cases. Regan (1978) found interference even using only the first letter of a conflicting color word (e.g., the letter B in red ink). Nor do instructional manipulations have much impact.…”
Section: Variations On the Stroop Procedures The Stroop Color-word Intmentioning
confidence: 99%
See 1 more Smart Citation
“…First, Beech, Agar, and Baylis (1989) found that the Stroop effect from incongruent words disappears when compared with nonwords that share the first two letters with the incongruent word. In addition, other studies have reported that just the first two letters of an incongruent word are sufficient to produce interference effects (Bibi, Tzelgov, & Henik, in press;Coltheart, Woollams, Kinoshita, & Perry, 1999;Regan, 1978;Singer, Lappin, & Moore, 1975). From this, it appears that the absence ofa Stroop effect with this nonword condition is an expected pattern, rather than an exception.…”
Section: Discussionmentioning
confidence: 61%
“…This constraint could not be perfectly met. Care was taken, however, that none of the words had the same initial letter as the verbal label of the accompanying picture (for the importance of the first letter, see, e.g., Lupker, 1982;Posnansky & Rayner, 1977;Regan, 1978;and Singer, Lappin, & Moore, 1975). (3) In the distractor conditions, RELlNRS and UNRlNRS pictures were not to be combined with words that denote objects that show a large visual similarity to the target picture.…”
Section: Methodsmentioning
confidence: 99%